Uji Sitotoksisitas Fraksi Aktif dan Senyawa Murninya yang Dihasilkan oleh Kapang Endoiit Tanaman Obat dari Lombok Timur terhadap Sel MCF-7 - ERWAHYUNI ENDANG PRABANDARI; TUN TEDJA IRAWADI; WAHONO SUMARYONO (Fakultas Farmasi Universitas Pancasila, 2012)
Screening for citotoxicity has been conducted on 36 endophytic fungi isolated from medicinal plants in East Lombok. Isolates were cultivated in 100 mL potato dextrose yeast extract medium in 250 mL Erlenmeyer, incubated at 28°C and shaked in 150 rpm for 10 days. Broth was extracted with buthanol, ethyl acetate and dichloromethane. Extracts were concentrated under vacuum concentrator and assayed for citotoxicity against Artemia salina using the BSLT method. Screening using 100 mg/L of crude extract showed that 9 extracts were active out of 108 extracts assayed. Further screening based on LC50 showed that the ethyl acetate extract from fungus ENLT 74.3d.2 was the most active with LC 50=30.21 mg/L. Fungus was isolated from Cibotium barometz and described as Curvularia lunata. The most active extract was fractionated by column silica gel 60 and eluted using hexane, ethyl acetate, and methanol. These fractions showed that the ethyl acetate fraction was the most active fraction (LC50 = 4.69 mg/L). Purification was conducted by HPLC using column C18 and eluted by gradient system of acetonitril water 15% to 100% in 25 minutes. The active compound retention time was 14-16 min, λmax = 233 nm, and at 5 mg/L could inhibit 28% MCF-7 cell proliferation.